2007
DOI: 10.1117/1.2804078
|View full text |Cite
|
Sign up to set email alerts
|

Optical detection of intracellular cavitation during selective laser targeting of the retinal pigment epithelium: dependence of cell death mechanism on pulse duration

Abstract: Selective laser targeting of the retinal pigment epithelium (RPE) is an attractive method for treating RPE-associated disorders. We are developing a method for optically detecting intracellular microcavitation that can potentially serve as an immediate feedback of the treatment outcome. Thermal denaturation or intracellular cavitation can kill RPE cells during selective targeting. We examined the cell damage mechanism for laser pulse durations from 1 to 40 micros ex vivo. Intracellular cavitation was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 40 publications
0
43
0
1
Order By: Relevance
“…RPE cells are damaged thermomechanically by the formation of microbubbles by nanosecond and short microsecond pulses, while thermal damage, that is, coagulation, is observed with pulses of a few milliseconds and longer. The transition of photodisruption to photothermal denaturation occurs at exposure durations between 20 and 50 µs [41,42]. With SRT, axial and lateral heating of the tissue is confined to the absorbing RPE cells, whereas conventional photocoagulation is associated with strong heat diffusion into the neural retina and choroid with subsequent scotoma and scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…RPE cells are damaged thermomechanically by the formation of microbubbles by nanosecond and short microsecond pulses, while thermal damage, that is, coagulation, is observed with pulses of a few milliseconds and longer. The transition of photodisruption to photothermal denaturation occurs at exposure durations between 20 and 50 µs [41,42]. With SRT, axial and lateral heating of the tissue is confined to the absorbing RPE cells, whereas conventional photocoagulation is associated with strong heat diffusion into the neural retina and choroid with subsequent scotoma and scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…7,11,25 Studies have also shown that the microcavitation thresholds decrease with increasing number of pulses. 26 The RPE is believed to be the site for threshold damage for all nanosecond and picosecond laser exposures in the visible and NIR.…”
Section: Mechanisms Of Short-pulsed Laser-inducedmentioning
confidence: 99%
“…11 The RPE is a monolayer of cells located within the retina. Melanin-containing organelles known as melanosomes, found in RPE cells, readily absorb ∼50 to 60% of the incident visible light as well as NIR radiation.…”
Section: Retinal Pigment Epithelium and Melanosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology of such lesions clearly demonstrates damage to the photoreceptors. While 10 ms pulses might have been "shown to achieve effective and safe laser treatments," a selective effect in terms of targeting only the RPE can only be achieved with thermo-mechanical effects following pulse durations < 50 µs (Schuele et al 6 and Lee et al 7 ). When using longer pulse durations, purely selective thermal effects can hardly be achieved owing to the nature of heat diffusion, except when neighboring cells have different resistance to heat, which to the best of our knowledge is not the case between RPE and photoreceptor cells.…”
Section: Framme and R Brinkmannmentioning
confidence: 99%